Relationship between images and fiction in Jacques Rancière’s thought - Soto Calderón, Andrea (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This article explores the relationship between image and fiction in Jacques Rancière’s thought. Rancière has reflected on the concept of fiction at great length. Using a diverse range of materials, he has examined the critical potential of fiction in configuring litigious scenes of the common, in questioning identity logics and in disputing an established order. However, critics of these developments have mainly focused on the relationship between fiction and politics or between fiction and literature, virtually ignoring the unique relationship between images and fiction.